Comparison of dosimetric parameters derived from whole organ and wall contours for bladder and rectum in cervical cancer patients treated with intracavitary and interstitial brachytherapy. Issue 3 (June 2018) - Gerber, Rachel; Rink, Alexandra; Croke, Jennifer; Borg, Jette; Beiki-Ardakani, Akbar; Fyles, Anthony; Milosevic, Michael; Xie, Jason; Keller, Harald; Han, Kathy
Abstract: For volumes up to 2 cm 3 of the bladder and possibly up to 5 cm 3 of the rectum, doses computed from the whole organ were good estimates of the doses in the wall in cervix brachytherapy, and there were no significant differences between patients treated with or without interstitial needles.